A Review of Body Composition Measurement in the Assessment of Health. Issue 1 (January 2015) - Toomey, Clodagh M.; Cremona, Alexandra; Hughes, Katie; Norton, Catherine; Jakeman, Phil
<x xml:space="preserve">Abstract</x> The measurement of human body composition plays an important role in qualifying health and nutritional status, the impact of disease, and change due to nutritional, therapeutic, or behavioral intervention. The accurate identification of those with either normal or nonnormal components of body composition requires an understanding of the available methods. Over the last century, the qualifying assumptions, accuracy, and precision of a variety of direct and indirect techniques of body composition measurement have been reported in the extant literature. This review provides a summary of current technological advances in the measurement of human body composition and an overview of research- and field-based methods that are relevant to the health care professional in a clinical setting.